2023
DOI: 10.1177/11795549231206796
|View full text |Cite
|
Sign up to set email alerts
|

Is the Urinary and Gut Microbiome Associated With Bladder Cancer?

Joanna Chorbińska,
Wojciech Krajewski,
Łukasz Nowak
et al.

Abstract: Background: Microbiome dysbiosis plays a role in the pathogenesis of many urological diseases, including bladder cancer (BC). The aim of the study was to compare the urinary and gut microbiota of patients with BC with a healthy control (HC) group. Methods: The study group included patients hospitalized in 2020 to 2021 with diagnosed BC and HC. Prior to the transurethral resection of bladder tumor, patients collected their urine and stool which was then subjected to 16S rRNA gene sequencing. Results: Overall, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…They also found that patients with high-diversity microbiota at baseline exhibited greater median change in pH compared to those with low-diversity attributes. These findings are also reiterated by a recent systematic review (Chorbinska et al, 2023).…”
Section: Discussionsupporting
confidence: 55%
“…They also found that patients with high-diversity microbiota at baseline exhibited greater median change in pH compared to those with low-diversity attributes. These findings are also reiterated by a recent systematic review (Chorbinska et al, 2023).…”
Section: Discussionsupporting
confidence: 55%